Análise ambiental como ferramenta para conservação de acervos: estudo de caso do Museu Arqueológico da Região de Lagoa Santa - Beatriz Maria Fonseca Silva (2016)
This paper investigates the appropriate environmental conditions to objects exhibition. It's inserted in the context of Preventive Conservation of Cultural Heritage and explores the temperature and humidity monitoring as a diagnostic tool, showing the importance of surrounding layers analysis around the object: the macro environment, the building, the exhibition room, the display and the support. It also emphasizes the importance of post studies measurements, through tables, graphical interpretation and correlation of these with constructive and geographical features of the investigated site. The case study is the Archaeological Museum of Lagoa Santa, located in the State of Sumidouro Park, a federal conservation unit belonging to sustainable use of natural resources category of the APA Lagoa Santa Karst, in Minas Gerais, Brazil. This region is scene of major archaeological researches since 1835, when the danish naturalist Peter Lund explored the location. The Museum is a cultural landmark in the region and has a closely related with the local community. This survey assesses the international parameters indicated in the theoretical bases as suitable for collections conservation, correlating it with the peculiarities of the studied site, emphasizing the need for research in the brazilian context . The results of the investigations show mainly the vulnerability of the building and the collection front the influence of humidity and temperature, presents in the local climate. It can be considered that the proper maintenance of both the building as objects, and suitable packaging are are essential to the conservation of MARLS's collections.